Cadmium-Responsive Thiols in the Ectomycorrhizal Fungus Paxillus involutus - Courbot, Mikael (American Society for Microbiology, 2004)
Molecular and cellular mechanisms underlying the sustained metal tolerance of ectomycorrhizal fungi are largely unknown. Some of the main mechanisms involved in metal detoxification appear to involve the chelation of metal ions in the cytosol with thiol-containing compounds, such as glutathione, phytochelatins, or metallothioneins. We used an improved high-performance liquid chromatography method for the simultaneous measurement of thiol-containing compounds from cysteine and its derivatives (γ-glutamylcysteine, glutathione) to higher-molecular-mass compounds (phytochelatins). We found that glutathione and γ-glutamylcysteine contents increased when the ectomycorrhizal fungus Paxillus involutus was exposed to cadmium. An additional compound with a 3-kDa molecular mass, most probably related to a metallothionein, increased drastically in mycelia exposed to cadmium. The relative lack of phytochelatins and the presence of a putative metallothionein suggest that ectomycorrhizal fungi may use a different means to tolerate heavy metals, such as Cd, than do their plant hosts.